Unsteady free convection on a horizontal circular cylinder in the presence of heat generation and radiation - Zainuddin, Najahulfazliah (2014)
The unsteady free convective ﬂow about a horizontal circular cylinder in the presence of heat generation and radiation is considered in this thesis. The cylinder is ﬁxed and immersed in a Newtonian ﬂuid, while the temperature at the surface is either heated uniformly or oscillated harmonically about the mean temperature, temperature of the surrounding. In this study, the governing equations are ﬁrst transformed into a non-dimensional form by using appropriate non-dimensional variables. These equations are then transformed into a system of nonlinear partial differential equations, then were solved numerically by using two types of ﬁnite difference methods namely explicit ﬁnite difference method and implicit ﬁnite difference scheme of Crank Nicolson method. The solutions obtained by those two methods are used to compare the accuracy between them with the previous studies. The presence of heat generation signiﬁcantly gives effect which increased the local skin-friction coefﬁcient, temperature and velocity distribution but the local rate of heat transfer decreases. While, the presence of radiation increase the local rate of heat transfer, skin-friction coefﬁcient, the temperature and velocity distributions. On the other hand, as the Prandtl number increases, the temperature and velocity distributions are decreases. This study also presents the temperature patterns for the problems when the temperature of the surface is heated and oscillated with respect to time. The comparison between the presence of radiation, heat generation and both of radiation and heat generation on temperature proﬁles against time are presented. It would be interesting when this study extended by involving the effect of magnetic ﬁeld on this study and solve the related problems by using other numerical method.